The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/nag.3250
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear consolidation of soft foundation improved by prefabricated vertical drains based on elliptical cylindrical equivalent model

Abstract: This study builds up an elliptical cylindrical equivalent model (ECEM) of prefabricated vertical drains (PVD)‐improved foundation which incorporates the nonlinear variation of compressibility and permeability and the preconsolidate state of soil. An exact solution and a simplified solution are derived for the nonlinear consolidation model under a combined vacuum and surcharge preloading. Considering the stratification of improved soil and the reduction of vacuum pressure along PVD, a precise settlement predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The rapid development of human activities has a great influence on the surrounding environment, namely the rock and soil medium. 1,2 For example, engineering activities, such as ground improvement based on thermal approach, 3,4 construction of energy piles, 5,6 extraction and storage of geothermal energy, 7,8 disposal of radioactive waste underground, 9 pipeline transportation of submarine gas 10 and so on, will remarkably affect the thermo-hydro-mechanical (THM) response of the surrounding rock and soil media, which may induce large deformation, long-term deformation and even failure of the rock and soil foundation. 11,12 To solve the above engineering problems, increasing attention have been paid on the research of the THM coupling behaviour of multilayered media.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of human activities has a great influence on the surrounding environment, namely the rock and soil medium. 1,2 For example, engineering activities, such as ground improvement based on thermal approach, 3,4 construction of energy piles, 5,6 extraction and storage of geothermal energy, 7,8 disposal of radioactive waste underground, 9 pipeline transportation of submarine gas 10 and so on, will remarkably affect the thermo-hydro-mechanical (THM) response of the surrounding rock and soil media, which may induce large deformation, long-term deformation and even failure of the rock and soil foundation. 11,12 To solve the above engineering problems, increasing attention have been paid on the research of the THM coupling behaviour of multilayered media.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the consolidation theory has been developed by considering the well resistance, band-shaped PVD, nonlinear stress-strain relationship, vacuum preloading, vertical flow, layered soil, partially penetrating vertical drains, and other factors. [12][13][14][15][16][17][18][19][20] To replicate the realistic geometry of PVD in the consolidation model, an elliptical cylindrical equivalent model was devised by Huang et al 19 In previous studies, 21,22 the elliptical cylindrical equivalent model has been proved to be a generalized consolidation model since it could readily be converted into the typical circular cylindrical equivalent model. Also, previous studies have validated the equivalent elliptical cylindrical model by comparing it to other equivalent models and a large number of measured data.…”
Section: Introductionmentioning
confidence: 99%
“…The variance of temperature field has a great influence on the surrounding rock and soil medium, which is reflected by the change of its physical and mechanical properties. [1][2][3][4] With more engineering problems being reported, such as geothermal energy extraction and storage, 5,6 radioactive waste disposal, 7 deep drilling and excavation, 8 energy piles, [9][10][11][12] ground improvement using prefabricated vertical thermal drains, [13][14][15] research on the thermo-hydro-mechanical (THM) coupling process has received increasing attention. Among them, thermal consolidation of saturated media is one of the most widely researched and yet not fully understood aspects in the field of geotechnical engineering.…”
Section: Introductionmentioning
confidence: 99%
“… show the influence of thermo-osmotic coefficient S w on the development of pore water pressure and displacement for different contact models. FromFigures 11,13,15, and 17, it is found that all the excess pore water pressures calcaulated by the four models decrease sharply as the thermo-osmotic coefficient decreases. It is also found that the maximum excess pore water pressures obtained by the perfect contact model for different thermo-osmotic coeffecients are at the interface, but those obtained by the other three models are in the first layer.…”
mentioning
confidence: 96%